2006
DOI: 10.1253/circj.70.342
|View full text |Cite
|
Sign up to set email alerts
|

CC Chemokine Receptor-2 Deficiency Attenuates Oxidative Stress and Infarct Size Caused by Myocardial Ischemia-Reperfusion in Mice

Abstract: arly coronary reperfusion limits myocardial damage and improves survival after myocardial infarction. However, growing evidence indicates that reperfusion itself can cause damage to the ischemic myocardium; this damage is known as post-ischemic myocardial reperfusion injury. 1 Local and systemic inflammatory reactions play a key role in the extension of myocardial tissue injury and adverse effects during left ventricular (LV) recovery. 2 Some experimental studies have demonstrated the importance of monocyte/ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 48 publications
4
64
1
1
Order By: Relevance
“…Hayasaki et al reported that a reduction in myocardial oxidative stress was associated with attenuation of IR injury in mice deficient in the CC chemokine receptor 2. 24 The discrepancy between the study by Hayasaki et al and the present study regarding the influence of oxidative stress on IR injury may derive from differences in the animal model used or the timing for the evaluation of oxidative stress. Nonomura et al, however, showed no significant relation between oxidative stress and IR injury in rats treated with cardiac sympathetic denervation.…”
Section: Antioxidant Property Of Fvcontrasting
confidence: 68%
“…Hayasaki et al reported that a reduction in myocardial oxidative stress was associated with attenuation of IR injury in mice deficient in the CC chemokine receptor 2. 24 The discrepancy between the study by Hayasaki et al and the present study regarding the influence of oxidative stress on IR injury may derive from differences in the animal model used or the timing for the evaluation of oxidative stress. Nonomura et al, however, showed no significant relation between oxidative stress and IR injury in rats treated with cardiac sympathetic denervation.…”
Section: Antioxidant Property Of Fvcontrasting
confidence: 68%
“…[7][8][9] Physiological concentrations of NO produced from endothelial NO synthase (eNOS) or NO donors exert significant cardioprotective effects, whereas the reaction between NO and ROS produces peroxynitrite and results in oxidative and nitrative tissue injury. [7][8][9][10][11][12][13] Evidence from several model systems supports the notion that NO radicals cause myocardial damage in MIR, 7,8,[12][13][14][15] whereas a small amount of NO exerts a cytoprotective effect in the reperfused heart. 11,12,16,17 The dynamics of oxidative stress up to 48 h after MIR remain unclear because of the difficulties associated with monitoring oxidation in vivo.…”
mentioning
confidence: 72%
“…[7][8][9][10] Though NO itself is not toxic and does not induce tissue injury, even at a high concentration, the reaction between NO and ROS produces peroxynitrite and results in oxidative and nitrative tissue injury. [8][9][10][11][12][13] Huang et al showed that the inhibition of iNOS activity blocks the increase in the number of leukocytes that synthesize ROS after MIR. 40 In the present study, we demonstrated that the urinary and tissue biopyrrins concentrations were obviously reduced with nonselective suppression of NOS expression.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Recently, it has Circulation Journal Vol. 72, October 2008 been demonstrated that the expression of MCP-1 in the myocardium increases during the early phase of MI, 5,10,[16][17][18] and that targeted deletion or pharmacological inhibition of MCP-1 prevents early post-MI LV remodeling. 17,19 However, the role of myocardial MCP-1 during the chronic phase of MI remains to be elucidated.…”
mentioning
confidence: 99%